Thermally induced structure evolution on the corrosion behavior of Al-Ni-Y amorphous alloys. (November 2018) - Zhang, L.M.; Zhang, S.D.; Ma, A.L.; Hu, H.X.; Zheng, Y.G.; Yang, B.J.; Wang, J.Q.
Graphical abstract: Highlights: Structure evolution caused significant changes in corrosion behavior. Annealing below T g enhanced the corrosion resistance by reducing free volume. Corrosion behavior was closely related to nanocrystal size for partial annealing. Distinct composition difference was detected with the increase of nanocrystal size. Fermi level and work function of passive film were changed with structure evolution. Abstract: The effect of thermally induced structural evolution on the corrosion behavior of Al-Ni-Y amorphous alloys was investigated. Structural relaxation annealing significantly enhanced the corrosion resistance of Al-Ni-Y alloys, and the main reason was attributed to the decreased free volume promoting the formation of a highly protective passive film. The corrosion behavior of Al-Ni-Y alloys was closely associated with nanocrystal size after partially devitrified annealing. The larger nanocrystals caused more obvious composition heterogeneity around the nanoscale precipitates, deteriorating the corrosion resistance. In addition, the component and energy band of the passive film on Al-Ni-Y alloys with structure evolution were also discussed.